THE ASSOCIATION BETWEEN KNOWLEDGE AND ATTITUDE TOWARDS COVID-19 AND INTEREST IN ONLINE LECTURE OF PRE-CLINIC AND CLINIC SECRETARIAT STUDENTS OF FACULTY OF MEDICINE - Muhammad Aziz; Pramadita Widya Garini (Majalah Kedokteran Sriwijaya, 2020)
Coronavirus diseases 2019 or COVID-19 have gotten the world’s attention since it’s first existencein Wuhan, China at the end of December 2019. COVID-19 has been considered as a pandemic by WHO by March 11th, 2020 and today it has brought several life aspects down, such as in economic, political, social, and education aspect. Distance learning (PJJ) either for school students or college students which applies an online method becomes the best solution for the impacted countries, including Indonesia. The purposes of distance/online lecture are to ensure that the teaching-learning process is still conducted based on curriculum outcomes target or university credit unit (SKS) and to prevent the COVID-19 cluster formed in schools. There are many factors affecting the effectiveness of online lecture, one of them is students’ interest to it. This study aimed to see the correlation between knowledge and attitude towards COVID-19 and interest in online lecture of pre-clinic and clinic secretariat students of the Faculty of Medicine of Universitas Sriwijaya in 2020. This study was observational analytic with a cross-sectional design. This study involved 101 respondents. The descriptive analysis results showed that most respondents were ? 21 years and female. The majority of preclinical and clinical clerkship students had a good level of knowledge (76.8% and 52.6%), a good attitude (74.4% and 57.9%), and a high interest in studying online (54.9% and 57.9%). The bivariate analysis results in this study showed a significant relationship between knowledge of COVID-19 and interest in online lectures in preclinical students and clinical clerkship (p=0.039 and p=0.005). Attitudes towards COVID-19 had a significant relationship with interest in online classes in preclinical students and clinical clerkship (p=0.041 and p=0.024).